Metabolite profiles and mass balance of fuzuloparib, a novel poly (ADP‐ribose) polymerase inhibitor, in subjects with advanced solid cancers - Bian, Yicong; Meng, Jian; Ma, Sheng; Li, Guangze; Wang, Yuya; Li, Shaorong; Liu, Linsheng; Huang, Chenrong; Zhang, Hua; Zhong, Dafang; Miao, Liyan (British journal of clinical pharmacology, 2022)
Aim This trial (NCT04013048) investigated the metabolite profiles, mass balance and pharmacokinetics of fuzuloparib, a novel poly (ADP‐ribose) polymerase inhibitor, in subjects with advanced solid cancers. Methods A single dose of 150 mg [14C]fuzuloparib was administered to five subjects with advanced solid cancers. Blood, urine and faecal samples were collected, analysed for radioactivity and unchanged fuzuloparib, and profiled for metabolites. The safety of the medicine was assessed during the study. Results The maximum concentrations (Cmax) of the total radioactivity (TRA) and unchanged fuzuloparib in plasma were 5.39 μg eq./mL and 4.19 μg/mL, respectively, at approximately 4 hours post dose. The exposure (AUC0‐t) of fuzuloparib accounted for 70.7% of the TRA in plasma, and no single metabolite was observed accounting for more than 10% of the plasma TRA. The recovery of TRA in excreta was 103.3 ± 3.8% in 288 hours, including 59.1 ± 9.9% in urine and 44.2 ± 10.8% in faeces. Sixteen metabolites of fuzuloparib were identified, including mono‐oxidation (M1), hydrogenation (M2), di‐oxidation (M3), trioxidation (M4), glucuronidation (M5, M7, M8) and de‐ethylation (M6) products, and there was no specific binding between these metabolites and blood cells. Aliphatic hydroxylated fuzuloparib (M1‐1) was the primary metabolite in the excreta, accounting for more than 40% of the dose for subjects. There were no serious adverse events observed in the study. Conclusion Fuzuloparib was widely metabolized and excreted completely through urine and faeces in subjects with advanced solid cancer. Unchanged fuzuloparib was indicated to be the primary drug‐related compound in circulation. [14C]fuzuloparib was well‐tolerated at the study dose.